An Analysis on the Denotative and Connotative Meaning of Lyrics of Creed’s Songs - Yulianus P Mangewa (AgroSainT, 2012)
Semantics as the study of meaning stands at the very center of the linguistic quest to understand the nature of language and human language abilities. It is obvious that semantics has an important role in understanding and comprehending a language, especially for English. Semantics not only concern with the study of meaning but also with the relationship between language and culture. Denotative meaning and connotative meaning: both of them are based on a relationship between words & world. Denotation is the meaning of a word which is primarily refers to the real word, the "dictionary definition” for instance “cow” shows a kind of animal, “house” shows a kind of building. Connotation meaning is the aspect of meaning added to the denotation of a word it relates to the association that a word has above its denotation. The connotative meaning differs from one society to another. Connotation may be subject to variable exchange from generation to the next. Connotation may be rather subjective and not shared in the same way by all speakers of a language. Our individual experience of language and its relation to the world is to some extent unique and idiosyncratic. Connotation is not stable. That Creed’s songs are analyzed using the descriptive qualitative approach in finding its denotative and connotative meaning. The data are taken from lyric of Creed’s songs which consists of 2 lyrics from different albums such as My Sacrifice and Don’t Stop Dancing. The writer chooses those lyrics because it contains allusion and a popularly Christian theological concept, of absolute individual belief, usually Monotheistic. It also focuses on questions of faith, Christianity, and eternity. Finally, the writer suggests to the next writer whom want to concern with the similar topic to analyze denotative and connotative meaning that can be found in newspaper and advertisement on Television etc.